Ahmet Ağaoğlu’nun İrşad Gazetesi’ndeki yazıları (1905-1906) - Asadov, Chingiz (My University, 2019)
Karabağ’ın Şuşa kentinde doğan Ahmet Ağaoğlu (1869-1939), döneminin en önemliKarabağ’ın Şuşa kentinde doğan Ahmet Ağaoğlu (1869-1939), döneminin en önemli gazetecisi, fikir ve siyaset adamlarından biri olan, önemli bir şahsiyettir. Daha öğrencilik yıllarında Fransa’da başladığı yazarlık faaliyetine, Kafkasya’ya döndükten sonra da “halkının cehaletten kurtulması” ve onların haklarının müdafaası için daha yoğun bir şekilde devam etmiştir.

Ahmet Agaoglu (1869-1939), who was born in the Shusha region of Karabakh, is the most important journalist of his time, a distinguished person who is one of the ideas and politicians. He started her writing career in France when he was still a student.After his return to the Caucasus, he continued to do more intensely to free his people from ignorance and to defend their rights.
Keywords: 20. yy; 20th century; Ahmet Bey Aghayev; Ahmet Bey Ağayev; Armenians; Caucasus; Ermeniler; History; Irshad Newspaper; Islam; İrşad; İslam; Kafkasya; Muslims; Müslümanlar; Russia; Rusya; Tarih; Turkey; Türkiye